Implementation of Learning Strategies based on Reflective Learning Theory to Improve Studentsâ Self-Efficacy in Learning English - Hidayati, Ratri Nur (Universitas Ahmad Dahlan, 2015)
Self-Efficacy means the belief in ones capabilities to achieve a goal or an outcome. Efficacy beliefs play an influential meditational role in academic attainment. While Reflective learning can be described as tending to think deeply about the knowledge obtained by study. Reflection is the indication of deep learning because it helps students learn through reflection, precisely because of the established link between reflection and deeper learning. Reflective learning is closely related to improve Self-efficacy. Thus this article aims at elaborating the effective English learning strategies based on reflective learning theory to improve studentsâ self- efficacy. This paper proposes some actions, i.e. implementing oral reflective learning on action, oral reflective learning in action and written reflective learning. In improving the studentsâ self-efficacy in learning in the forms of (1) the improvement of studentsâ appreciation of social resources, (2) the improvement of studentsâ courage in achieving academic performances, (3) the improvement of studentsâ consistency for self- regulated learning, and (4) the improvement of studentsâ social self-efficacy.Â